2009
DOI: 10.1016/j.applthermaleng.2008.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Transient temperature field in a parallel-flow three-fluid heat exchanger with the thermal capacitance of the walls and the longitudinal walls conduction

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It is stated in the study that axial heat conduction along the dividing walls often plays some role and cannot be neglected. Malinowski and Bielski [15] studied the problem of transient and steady-state behavior of a parallel-flow three-fluids heat exchanger with regard to the transverse and axial wall conduction. They showed that good thermal conductivity of the wall increases the influence of axial heat conduction and at the same time decreases the effect of resistance in transverse direction.…”
Section: Introductionmentioning
confidence: 99%
“…It is stated in the study that axial heat conduction along the dividing walls often plays some role and cannot be neglected. Malinowski and Bielski [15] studied the problem of transient and steady-state behavior of a parallel-flow three-fluids heat exchanger with regard to the transverse and axial wall conduction. They showed that good thermal conductivity of the wall increases the influence of axial heat conduction and at the same time decreases the effect of resistance in transverse direction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, they further set up the numerical model [23] that takes into account the thermal capacitance of the walls, the longitudinal heat conduction through the walls, and the conductive resistance across the walls to study the transient temperature response of the parallel three-fluid heat exchanger.…”
Section: Introductionmentioning
confidence: 99%
“…As we know, three-fluid heat exchanger is a type of heat exchangers which can transfer heat synchronously between three fluids. It has been used in cryogenics, aerospace and chemical industries [16,17]. The application of three-fluid heat exchangers in these fields makes the equipments more compact in construction, higher in thermal efficiency [18] and lower in reliability risk [19].…”
Section: Introductionmentioning
confidence: 99%
“…Analytical solution was obtained for special cases [21]. Finite element models were developed for some types of three-fluid heat exchangers, including co-current parallel flow [22,23], countercurrent parallel flow [17,[22][23][24][25] and cross parallel flow [26][27][28]. Integral-mean temperature difference model has also been developed to simplify the simulation of three-fluid heat exchangers [18].…”
Section: Introductionmentioning
confidence: 99%